Unique Transcriptome, Pathways, and Networks in the Human Endometrial Fibroblast Response to Progesterone in Endometriosis - Aghajanova, L.; Tatsumi, K.; Horcajadas, J. A.; Zamah, A. M.; Esteban, F. J.; Herndon, C. N.; Conti, M.; Giudice, L. C. (Biology of reproduction, 2011)
Eutopic endometrium in endometriosis has molecular evidence of resistance to progesterone (P(4)) and activation of the PKA pathway in the stromal compartment. To investigate global and temporal responses of eutopic endometrium to P(4), we compared early (6-h), intermediate (48-h), and late (14-Day) transcriptomes, signaling pathways, and networks of human endometrial stromal fibroblasts (hESF) from women with endometriosis (hESF(endo)) with hESF from women without endometriosis (hESF(nonendo)). Endometrial biopsy samples were obtained from subjects with and without mild peritoneal endometriosis (n = 4 per group), and hESF were isolated and treated with P(4) (1 μM) plus estradiol (E(2)) (10 nM), E(2) alone (10 nM), or vehicle for up to 14 days. Total RNA was subjected to microarray analysis using a Gene 1.0 ST (Affymetrix) platform and analyzed by using bioinformatic algorithms, and data were validated by quantitative real-time PCR and ELISA. Results revealed unique kinetic expression of specific genes and unique pathways, distinct biological and molecular processes, and signaling pathways and networks during the early, intermediate, and late responses to P(4) in both hESF(nonendo) and hESF(endo), although a blunted response to P(4) was observed in the latter. The normal response of hESF to P(4) involves a tightly regulated kinetic cascade involving key components in the P(4) receptor and MAPK signaling pathways that results in inhibition of E(2)-mediated proliferation and eventual differentiation to the decidual phenotype, but this was not established in the hESF(endo) early response to P(4). The abnormal response of this cell type to P(4) may contribute to compromised embryonic implantation and infertility in women with endometriosis.